1999
DOI: 10.1007/s11589-999-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Rupture process of the M L=4.1 earthquake in Huailai Basin on July 20, 1995

Abstract: On July 20, 1995, an earthquake of ML=4.1 occurred in Huailai basin, northwest of Beijing, with epicenter coordinates 40.326°N, 115.448°E and focal depth 5.5 km. Following the main shock, seismicity sharply increased in the basin. This earthquake sequence was recorded by Sino-European Cooperative Huailai Digital Seismograph Network (HDSN) and the hypocentres were precisely located. About 2 hours after the occurrence of the main shock, a smaller event of ML=2.0 took place at 40.323°N, 115.447°E with a focal dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…Che et al (2001) suggest that the strength of the upper crust has been decreased by the action of hot fluids consistent with the small and moderate earthquake locations and the existence of hot springs in the region. Detailed modeling and moment tensor inversion for the Huailai M L event in 1995 (Xu et al, 1999(Xu et al, , 2001 led to a source depth estimate of 5.5 km again in the higher velocity layers of our model. Sun et al (1987) propose that the geothermal anomaly and tectonic extension are possibly related to the existence of the low-velocity layers.…”
Section: Model Comparison and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Che et al (2001) suggest that the strength of the upper crust has been decreased by the action of hot fluids consistent with the small and moderate earthquake locations and the existence of hot springs in the region. Detailed modeling and moment tensor inversion for the Huailai M L event in 1995 (Xu et al, 1999(Xu et al, , 2001 led to a source depth estimate of 5.5 km again in the higher velocity layers of our model. Sun et al (1987) propose that the geothermal anomaly and tectonic extension are possibly related to the existence of the low-velocity layers.…”
Section: Model Comparison and Discussionmentioning
confidence: 67%
“…An M L 4.1 earthquake occurred in the Yanqing-Huailai Basin on 20 July 1995, followed by approximately 450 aftershocks (Chen et al, 1998). Xu et al (1999Xu et al ( , 2001 and Chen et al (2005) have studied the rupture process and focal mechanism of this earthquake and the following earthquake sequence.…”
Section: Yanqing-huailai Basinmentioning
confidence: 99%
“…По нашим [12,26] и литературным данным [3,28,31,33] отмечается тенденция быстрого увеличения активности окислительного фермента пероксидазы у устойчивых растений после внедрения патогена, противоположная тенденция складывается у восприимчивых растений. Повышение ферментативной активности связано с мобилизацией защитных реакций у растений в ответ на проникновение возбудителя.…”
Section: физиолого-биохимические и физико-химические факторы определunclassified
“…3-n-Butylphthalide (NBP) [(±)-3-butyl-1(3H)-isobenzofuranone] was firstly isolated from Chinese herbs, including Apium graveolens, Ligusticum sinensis, and Liqusticum Chuanxiong Hort [1][2][3], and has also been obtained by chemical synthesis [4,5]. NBP is currently used clinically as a preferred drug for the treatment of ischemic stroke by increasing regional cerebral blood flow and inhibiting the release of glutamate and 5-hydroxytryptamine [6,7]. In addition, recent research has demonstrated that NBP displays beneficial effects by attenuating amyloid-induced cell death in neuronal cultures [8], improving cognitive deficits and preventing neuronal cell death after focal cerebral ischemia in mice [9,10] Abbreviations: C max , peak serum concentration; LLOQ, lower limit of quantification; ME, matrix effect; MRM, multiple reaction monitoring; NBP, 3-n-butylphthalide; QC, quality control; sCO 2 , supercritical carbon dioxide; SFC, supercritical fluid chromatography; T max , the time to reach the peak concentration and protecting cardiomyocytes from ischemia/reperfusioninduced apoptosis [11].…”
Section: Introductionmentioning
confidence: 99%